Effect of body mass index and chair height on the torque developed at the knee joint during back-to-sit and sit-to-stand movements. (2018) - Varghese, Jobin; Akhil, V.M.; Rajendrakumar, P.K.; Sivanandan, K.S.
Back-to-sit (BTS) and sit-to-stand (STS) are one among many vital functions of knee joint of human body. While designing bipedal robots, the knee joint should have the capacity to replicate the characteristics, such as that of human beings, especially the torque. The effect of weight and length as well as sitting chair height and speed of movement during BTS and STS has to be studied to limit the weight and height of robots or exoskeleton. Here we have used a camera and motion analysis software to acquire the data and studied the effect and interaction of body mass index and chair height on knee torque at various sitting speeds using two-way analysis of variance.